Murder in a lavender daze - Gerber, Daryl Wood (Gerber, Daryl Wood. Aroma wellness mystery, 2026)
"With its soothing décor and tempting treatments, customers are flocking to Aroma Wellness for more than just facials and massages. Lately, Emma has been booking private events, from spa parties to bridal showers and birthdays. Next on her calendar is something really unique: A "Happily Divorced" party. After eight years of marriage, Addison Lacey is divorcing her husband, whom she claims convinced her he was Mr. Nice Guy when he was really Mr. Controlling Guy. To kick off her journey toward becoming a better version of herself, Addison wants to celebrate, bigtime. Her wealthy mother, Gianna, a former model turned difficult diva, is footing the bill. . . . But when Emma goes to Gianna's home to pick up the final payment, she and Addison find her dead in her bed amid the aroma of lavender, with an herbal-infused pillow from the party nearby. Soon, Addison is a prime suspect. But Emma knows there are plenty of others Gianna rubbed the wrong way, including her soon-to-be ex-son-in-law. Once again, with the help of her cousin, her nana, and her trusted Birman cat, Vivi, Emma is determined to sniff out a killer--whether the police like it or not . . ."--Amazon.